VALUE APPROACH IN PROFESSIONAL TRAINING OF MUSIC TEACHERS - Byelikova, O.A. (Pedagogy of Higher and Secondary Education, 2009)
The author of an article reveal scientific approach () in the future musician-teacher's vocational training.